1987
DOI: 10.1016/0020-7292(87)90009-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of steroid receptors in ovarian neoplasms

Abstract: Estrogen and progesterone receptors were estimated in a total of 25 ovarian neoplasms. None of the benign tumors showed steroid receptors. In malignant tumors serous tumors were more often receptor positive than the mucinous. Receptor levels were correlated with the staging of the disease, menstrual status and the resectability of the tumor. The response to chemotherapeutic drugs was better in patients with low estrogen and progesterone receptors as compared to those with high levels. The latter group showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
3
9
0
Order By: Relevance
“…In our study, ER expression is positive in 4/11 cases (36.3%) cases, PR expression is positive in 5/11 (45.4%), which coincides with study of Sylvia et al [27] ER, PR has strong expression in endometrioid (2/3, 66.6%) and high-grade serous tumours (3/5 cases, 80%) which is similar to findings of Agarwal et al [28] Damia et al [29] This is in contrast to Buchynska et al [30] , who stated that ER expression is lower in high-grade tumour. The above features suggest possible mitogenic role of ER in ovarian tumours and high PR positivity in conjunction with ER expression is indicative of oestrogen regulated disease.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, ER expression is positive in 4/11 cases (36.3%) cases, PR expression is positive in 5/11 (45.4%), which coincides with study of Sylvia et al [27] ER, PR has strong expression in endometrioid (2/3, 66.6%) and high-grade serous tumours (3/5 cases, 80%) which is similar to findings of Agarwal et al [28] Damia et al [29] This is in contrast to Buchynska et al [30] , who stated that ER expression is lower in high-grade tumour. The above features suggest possible mitogenic role of ER in ovarian tumours and high PR positivity in conjunction with ER expression is indicative of oestrogen regulated disease.…”
Section: Discussionsupporting
confidence: 81%
“…[21] Agarwal et al reported that receptor positivity increases with stage of tumour. [20] Similar observations were made by Sylvia et al…”
Section: Section: Pathology Discussionsupporting
confidence: 79%
“…Hence ER/PR expression was more among postmenopausal patients as compared to premenopausal patients. Similar results were found in studies conducted by Sylvia et al, Hahnel et al and Agarwal et al [18][19][20] As per staging, ER was expressed as 66.66% in stage III, 66.66% in stage II, 50% in stage I. PR was expressed as 100 % in stage III, 100% in stage II and 25% in stage I. Hogdall E V et al reported that ER positivity in ovarian cancers increases with increasing FIGO stage. [21] Agarwal et al reported that receptor positivity increases with stage of tumour.…”
Section: Section: Pathology Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Agarwal et al [18] reported that low ER status correlated important, depending on the stage of the tumor. Glavind and Grove [14] reported that ER status varied significantly with an increasing response to chemotherapy, although this finding did not retain statistical significance in regard to among the various epithelial ovarian cancers.…”
Section: Tein (34 Months) (P å 0015) Five-year Survival In the Formermentioning
confidence: 98%